The Old Roman World : the Grandeur and Failure of Its Civilization. - Lord, John, 1810-1894 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Old Roman World: The Grandeur and Failure of Its Civilization" by John Lord is a historical account written during the late 19th century. The book explores the rise and fall of Roman civilization, emphasizing its military conquests, governmental structures, cultural achievements, and eventual decline. Lord sets out to illustrate both the greatness and the internal flaws of the Roman Empire, engaging with themes of ambition, war, governance, and morality. At the start of the book, the author introduces the epic tale of Rome's transformation from a small village into a mighty empire, detailing the aggressive military campaigns and the remarkable resilience of its citizen-soldiers. His narrative outlines the early heroic periods, intense struggles, and the singular dedication of Romans to warfare. Lord presents a vivid portrayal of the Roman character, portrayed as resilient and fiercely patriotic, driven more by a thirst for conquest than ideals of liberty or cultural enrichment. He sets the stage for a deeper analysis of various aspects of Roman life, its governmental constitution, and the societal dynamics that contributed to its expansion as well as its eventual downfall, which he plans to explore in subsequent chapters. (This is an automatically generated summary.)
Release date is 2004-11-01
Produced by Robert Nield, Tom Allen, Tiffany Vergon, Charles Aldarondo, Charles Franks and the Online Distributed Proofreading Team
Keywords: Rome -- Civilization